The impact of seven macroprudential policy instruments on financial stability in six euro area economies - Eva Lorenčič; Mejra Festić (Review of Economic Perspectives, 2021)
The aim of this paper is to investigate whether macroprudential policy instru-ments can influence the credit growth rate and hence financial stability. We use a fixed effects panel regression model to test the following hypothesis for six euro area econo-mies (Austria, Finland, Germany, Italy, Netherlands and Spain) during time span 2010 Q3 to 2018 Q4: "Macroprudential policy instruments (degree of maturity mismatch; in-terbank loans as a percentage of total loans; leverage ratio; non-deposit funding as a per-centage of total funding; loan-to-value ratio; loan-to-deposit ratio; solvency ratio) en-hance financial stability, as measured by credit growth". Our empirical results suggest that the degree of maturity mismatch, non-deposit funding as a percentage of total funding, loan-to-value ratio and loan-to-deposit ratio exhibit the predicted impact on the credit growth rate and therefore on financial stability. On the other hand, interbank loans as a percentage of total loans, leverage ratio, and solvency ratio do not exhibit the expected impact on the response variable. Since only four regressors (out of seven) have the signs predicted by our hypothesis, we can only partly confirm it.
Keywords: E58; G28; E60; E44; 330; Macroprudential policy; macroprudential instruments; systemic risk; finan-cial stability